Pengelolaan Kelas Yang Dinamis Sebagai Daya Tarik Motivasi Belajar Siswa Di SD Negeri Sampangan No. 26 Tahun 2016 - Nur Fikawati, Arian; , Minsih, S.Ag., M.Pd (2017)
Dynamic classroom management will be the main attraction for students to motivate them to learn. Learning will be more fun and to attract students when managing a dynamic class can be optimally managed by the teacher. This study aims to determine the dynamic classroom management in primary schools Sampangan No. 26 which include different types of classes, learn together in a group, to streamline the board, streamline student seating position and take advantage of the school library. In addition to knowing the appeal of student motivation during the learning process. This research uses a qualitative research, with the subjects that teachers class I to class V. In this study conducted in-depth interviews, observation and documentation. Furthermore, the data that have been collected are described, analyzed and processed with the appropriate theoretical as well as with the relevant peneitian. Management of dynamic classes bring a positive impact for students among which students become more active, students do not feel bored and tired, the students become more enthusiastic to go to school and receive lessons. So it will be an attraction for students' motivation to learn at school.